Investigation of the Effect of 3D Meniscus Geometry on Fluid Dynamics and Crystallization via In Situ Optical Microscopy‐Assisted Mathematical Modeling. Issue 1 (20th October 2021) - Lee, Jeong‐Chan; Seo, Hyeji; Lee, Minho; Kim, Dongjae; Lee, Hyeon Seok; Park, Hyunmin; Ball, Nathaniel; Woo, Junhee; Kim, Su Yeong; Nam, Jaewook; Park, Steve
Abstract: Solution‐based thin‐film solidification is a complex process involving various transport phenomena that are intricately dependent on multiple experimental parameters. The difficulty of analyzing this process experimentally or conducting exact numerical simulation make it challenging to understand, predict, and control the solidification process. In this work, a simple and effective technique to analyze the thin‐film solidification process during solution shearing, based on 3D geometrical model of the meniscus, is proposed. The 3D meniscus geometry, which changes depending on the experimental parameters, is attained using high‐speed side‐view and top‐view in situ microscopy. Thereafter, mass and momentum transport mathematical models are applied to obtain numerical solutions of transport phenomena within the meniscus. Utilizing these results, the underlying mechanism of dendritic growth of small molecule organic semiconductor is elucidated, which has previously been unknown. The 3D meniscus modeling is particularly important for this analysis, as dendrite formation is strongly dependent on the meniscus geometry near the contact line and mass transport variation perpendicular to the coating direction. This technique enables the study of complex relationship between experimental parameters and solidification process, which is widely applicable to various materials and coating systems; whereby, better understanding of thin‐film growth and device performance optimization is possible. Abstract : The 3D geometrical model of the meniscus is attained using high‐speed side‐view and top‐view in situ microscopy, within which a mathematical model for momentum and mass transport is developed. Utilizing 3D meniscus geometry, the underlying mechanism of dendritic growth of small molecule organic semiconductors is elucidated, which is widely applicable to various materials and coating systems.